Quality indicators in pediatric colonoscopy in a low-volume center: Implications for training - Lee, Way Seah; Tee, Chun Wei; Koay, Zhong Lin; Wong, Tat Seng; Zahraq, Fatimah; Foo, Hee Wei; Ong, Sik Yong; Wong, Shin Yee; Ng, Ruey Terng (Baishideng Publishing Group, 2018)
AIM To study implications of measuring quality indicators on training and trainees’ performance in pediatric colonoscopy in a low-volume training center. METHODS We reviewed retrospectively the performance of pediatric colonoscopies in a training center in Malaysia over 5 years (January 2010-December 2015), benchmarked against five quality indicators: appropriateness of indications, bowel preparations, cecum and ileal examination rates, and complications. The European Society of Gastrointestinal Endoscopy guideline for pediatric endoscopy and North American Society for Pediatric Gastroenterology, Hepatology and Nutrition training guidelines were used as benchmarks. RESULTS Median (± SD) age of 121 children [males = 74 (61.2%)] who had 177 colonoscopies was 7.0 (± 4.6) years. On average, 30 colonoscopies were performed each year (range: 19-58). Except for investigations of abdominal pain (21/177, 17%), indications for colonoscopies were appropriate in the remaining 83%. Bowel preparation was good in 87%. One patient (0.6%) with severe Crohn’s disease had bowel perforation. Cecum examination and ileal intubation rate was 95% and 68.1%. Ileal intubation rate was significantly higher in diagnosing or assessing inflammatory bowel disease (IBD) than non-IBD (72.9% vs 50.0% P = 0.016). Performance of four trainees was consistent throughout the study period. Average cecum and ileal examination rate among trainees were 97% and 77%. CONCLUSION Benchmarking against established guidelines helps units with a low-volume of colonoscopies to identify area for further improvement.